Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk Kesehatan Kulit - Zulhamdani Zulhamdani; Iswahyudi Iswahyudi; Ade Davy Wiranata (Pelantar Press, 2024)
Increased economic growth and people's lifestyles that have experienced a lot of shifts makes the need for beauty products increase, moreover this is also accompanied by the development of various skin diseases that are increasingly being found, this is caused by many people who want to look different, increased pollution , bad lifestyle and many other causes. Society as the target consumer company gets many choices of products offered from various corporate brands. It makes people have to be more careful in buying the products offered according to their needs and illness. Noting the above description, the researcher is interested in conducting a thesis research entitled